The Internet addiction test: Psychometric properties, socio-demographic risk factors and addictive co-morbidities in a large adult sample. (November 2021) - Sela, Yaron; Bar-Or, Ruth Lev; Kor, Ariel; Lev-Ran, Shaul
Highlights: This study examined psychometric properties of IAT among a sample of 4035 adults. Two-factor model was found indicating preoccupation and loss of control. Young age, not being married, and low socio-economic status predicted IA. Co-morbidity was found with drug and alcohol use, and other behavioral addictions. Abstract: The Internet Addiction Test (IAT) (Young, 1998) is one of the most utilized diagnostic instruments to evaluate internet addiction. Despite the wide use of IAT in research and clinical settings, there is lack of an empirical validation of this scale among a largescale adult population. The present study aimed to: (1) investigate the psychometric properties of a Hebrew version of the IAT among large-scale Israeli adult sample. (2) Assess the socio-demographic characteristics of individuals who suffer from IA. (3) Assess the co-morbidity of IA in relation to substance and behavioral addictions. A cross sectional study was conducted, by constructing a representative sample (N = 4035) of the Jewish adult (18–70 y/o, M = 40.5, SD = 14.5) population in Israel. Participants responded an online survey, that measured IAT, socio-demographic characteristics, substance and behavioral addictions. Results showed that two-factor model (Emotional and Cognitive Preoccupation with the Internet and Loss of Control and Interference with Daily Life) has good psychometric properties and fits the data well. Young age, not being married (Risk Ratio [RR] = 1.98, 95% CI [1.51–2.63]), and having a low socio-economic status (RR = 1.41, 95% CI [1.05–1.90]) were found to be associated with IA. Drug (RR = 4.50, 95% CI [2.89–7.01]) and alcohol (RR = 3.54, 95% CI [1.50–5.42]) use disorders were associated with IA. High co-morbidity between behavioral addictions and IA was also found (RR = 15.24, 95% CI [11.17–20.78]). Overall, results show that the Hebrew version of the IAT is a valid and reliable instrument, and provide a comprehensive picture of IA prevalence and profile in adult Israeli sample.